(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2020)
The study examines the motivation to visit religious site of Pashupatinath Area. Based on a structured questionnaire survey, the study sought if the three types of travel motivation, namely, construct motivation, religious motivation, and secular motivation push tourists to visit Pashupatinath. Using a purposive sampling technique 152 respondents who had stayed overnight in the hotels in Kathmandu Valley for Pashupati visit were successfully surveyed. The result revealed that secular motivation plays a significant role to visit the Pashupatinath followed by religious motivation. ANOVA found no significant relation between marital status and age group as to what motivate one to visit religious sites.